Total Antioxidant Activity of Plants of Symphytum L. Species - Vergun, Olena; Brindza, Jan; Rakhmetov, Djamal (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2020)
The aim of this study to demonstrate the antioxidant potential of methanolic, ethanolic and aqueous extracts of plants of Symphytum L. species. The DPPH radical scavenging effect was assessed by the discoloration of methanol solution of 2.2-diphenyl-1-picrylhydrazyl after 10 minutes according to Brand-Williams et al. (1995). Total antioxidant activity (TAA) of above-ground part of Symphytum asperum Lepech. during vegetation was from 73.59% (at spring vegetation stage) to 79.65% (fruiatage) in methanolic extracts, from 17.53% (budding stage) to 36.31% (spring vegetation stage) – in ethanolic extracts, from 59.64% (spring vegetation stage) to 76.15% (stage of stem growth) – in water extracts. Methanolic extracts of Symphytum caucasicum Bieb. showed the TAA from 75.48% (budding stage) to 80.81% (spring vegetation stage), ethanolic extracts – from 22.61% (blossoming stage) to 73.99% (spring vegetation stage), water extracts – from 67.46% (budding stage) to 74.45% (blossoming stage). In plant raw material of Symphytum × uplandicum Nyman TAA was from 16.24% (blossoming stage) to 79.18% (budding stage) in methanolic extracts, from 5.64% (blossoming stage) to 21.06% (budding stage) – in ethanolic extracts, from 17.23% (stage of stem growth) to 60.58% (budding stage) – in water extracts. Maximal sign of radical inhibition was noticed in methanolic extracts of Symphytum caucasicum in stage of spring vegetation and minimal – in ethanolic extracts of Symphytum × uplandicum in blossoming stage. Obtaned data allow to use these plants as plant raw material with antioxidant potential.